Researching problems in setting goals by students - L. V. Osipova; E. Yu. Chernyakevich (Вестник университета)
The article presents the results of an empirical study that reveals the problems of searching, understanding and setting goals by first year students. The study is relevant because it studies the psychological nature of the quality of students’ life in the process of their professional development, since the lack of goals among students is associated with dissatisfaction with life. The socio-psychological personality traits (The Giessen test), psychological defense mechanisms (Kellerman–Plutchik’s Life Style Index), the ability to set goals (D. A. Leontiev’s “Meaningful Life Orientations” methodology) were studied. The authors also analyzed the components of the students’ value-semantic sphere (author’s questionnaire). It is shown that the intensively working mechanisms of psychological defense, reducing the awareness of objective events, form features that impede the process of setting goals, and, consequently, the formation of mature personality traits. It was revealed that the presence of goals is associated with a positive social reputation of students.